Students' Opinions of the Use of Quipper School as an Online Learning Platform for Teaching English - Ramadhona, Nova; Ananda Alifia Putri; Dewi Sri Surya Wuisan (International Transactions on Education Technology (ITEE), 2022)
This article examines how students feel about using Quipper School as an e-learning platform to teach English and discusses its benefits and drawbacks. Using the cluster sampling approach and concentrating on the survey study method, this study used two sample classes with a total of fifty-three participants. Twenty questionnaires were sent out to students to gauge their opinions of Quipper School. When exploring the benefits and drawbacks of implementing Quipper School, which has been done through student interviews, in-depth information seems to be as significant as continuous responses. The results showed that pupils prefer to utilize IT and are at ease using it for educational purposes. More importantly, Quipper School's benefits encourage interaction between students and teachers both within and outside of the classroom. Even though the teacher isn't in the room, the pupils still receive instruction or have a chance to review the content. It uses a revolutionary learning approach to improve students' learning experiences. Quipper school also has drawbacks when used in the educational process, for instance, erratic internet connections, restricted computer resources that facilitate study at Quipper School, additionally, there was no spoken material that could be used in a prep school. Today, employing a quipper school to teach English might be beneficial for studying and teaching. Although the teacher is not physically present to give direct instruction, students still receive a lesson, and by studying the information whenever and wherever they are, they can increase their success in learning English.